Surface-wave velocity measurements of shear stiffness of moving earthflows - Berti, Matteo; Bertello, Lara; Squarzoni, Gabriela (Landslides, 2019)
Earthflows are a flow-like movement of plastic clayey soils characterized by long periods of slow motion (at rates averaging a few meters per year or less) alternated with short periods of rapid surges at high velocity (up to meters per hour). During rapid surges, most earthflows move over a long distance with a fluid-like behavior. Although the generation of flow-type failures is an important issue for hazard assessment, our knowledge is limited by the difficulty of monitoring the process in the field. This has led to different explanations for rapid earthflows including high pore–pressure generation along the basal slip surface, pervasive shearing, or material fluidization. One key question is whether or not earthflows can fluidize through remolding and water entrainment. If this occurs, the material can change from plastic to fluid as the soil moisture increases, causing the landslide to move as a viscous flow; if not, the material remains in a plastic state and, as suggested by many authors, the flow-like morphology shown by earthflows would result by distributed internal shears rather than real mass flow. In this study, we provide the first answer to this question by measuring the shear stiffness of four large active earthflows in the Northern Apennines of Italy. Shear stiffness was measured using two geophysical techniques, the multichannel analysis of surface waves (MASW) and the passive refraction microtremors (ReMi). Measurements were carried out just a few days after the mobilization of the landslides and repeated in the following 2–3 years to evaluate the change of elastic properties with time. Field data show that soon after the mobilization, earthflows are characterized by very low values of shear stiffness (about 5–15 MPa), typical of soft clay soils with the high-void ratio. Shear stiffness then increases 4–5 times in the following months (up to 40–60 MPa) as the earthflows slow down and the material consolidates. These data indicate that during a rapid movement, earthflows undergo a dramatic increase of porosity and water content that probably drive the transition from a solid to a fluid-like state.